2023
DOI: 10.1002/eat.23995
|View full text |Cite
|
Sign up to set email alerts
|

Time‐of‐day and day‐of‐week patterns of binge eating and relevant psychological vulnerabilities in binge‐eating disorder

Glen Forester,
Lauren M. Schaefer,
Dorian R. Dodd
et al.

Abstract: ObjectiveThe present study sought to characterize the temporal patterns of binge eating and theorized maintenance factors among individuals with binge‐eating disorder (BED).MethodEcological momentary assessment of 112 individuals and mixed‐effects models were used to characterize the within‐ and between‐day temporal patterns of eating behaviors (binge eating, loss of control only eating, and overeating only), positive and negative affect, emotion regulation difficulty, and food craving.ResultsRisk for binge ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Indeed, research has suggested trait-level moderators of the impact of emotions on binge eating in eating disorders (Culbert et al, 2016;Fischer et al, 2018), highlighting the potential utility of individual models. Time of day and contextual variables did not emerge as predictors of LOCE, despite research demonstrating that LOCE and binge eating are more likely to occur in the afternoon and evening (Forester et al, 2023). Results also failed to support our hypothesis that binge eating is more likely to occur when an individual is alone or at home.…”
Section: Predictors Of Loce and Overeating In Adolescentscontrasting
confidence: 81%
“…Indeed, research has suggested trait-level moderators of the impact of emotions on binge eating in eating disorders (Culbert et al, 2016;Fischer et al, 2018), highlighting the potential utility of individual models. Time of day and contextual variables did not emerge as predictors of LOCE, despite research demonstrating that LOCE and binge eating are more likely to occur in the afternoon and evening (Forester et al, 2023). Results also failed to support our hypothesis that binge eating is more likely to occur when an individual is alone or at home.…”
Section: Predictors Of Loce and Overeating In Adolescentscontrasting
confidence: 81%
“…First, we expanded our analyses to include purging and dieting in addition to binge eating. Nearly all the research to date on daily ER and disordered eating has focused on binge-eating phenotypes (Forester et al, 2023;Mikhail et al, 2022;Smith et al, 2021;Svaldi et al, 2019), with little known regarding how ER may impact other core disordered eating behaviors. Though ER difficulties are observed transdiagnostically across EDs (Brockmeyer et al, 2014;Prefit et al, 2019), evidence is more consistent regarding an association between NA and binge eating than NA and restrictive symptoms (Haedt-Matt & Keel, 2011;Haynos et al, 2015Haynos et al, , 2017Mikhail, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, family-related adverse life experiences (ALEs), especially early loss of caregivers, family separations, and detrimental parental interactions, negatively impact BN and BED patients [19]. Moreover, Forester and colleagues [20] demonstrated that specific times of the day (in particular, dinner time, but also lunch time and late evening) favour binge eating in BED patients, being the periods with the strongest food cravings and difficulties in emotional regulation.…”
Section: Introductionmentioning
confidence: 99%